The Euroization of Bank Deposits in Eastern Europe - Martin Brown; Helmut Stix (Oesterreichische Nationalbank (OeNB), 2014)
In Eastern Europe a substantial share of bank deposits are denominated in foreign currency. Deposit euroization poses key challenges for monetary policy and financial sector supervision. On the one hand, it limits the effectiveness of monetary policy interventions. On the other hand, it increases financial sector fragility by exposing banks to currency risk or currency induced credit risk. Policymakers disagree on whether Eastern European countries should tackle deposit euroization with "dedollarization" policies or should rather strive to adopt the Euro as their legal tender. Assessing the potential effectiveness of "dedollarization" policies requires a clear understanding of which households hold foreign currency deposits and why they do so. Based on survey data covering 16,375 households in ten countries in 2011 and 2012, we provide the first household-level analysis of deposit euroization in Eastern Europe. We examine how households' preferences for and holding of foreign currency deposits are related to individual expectations about monetary conditions and network effects. We also examine to what extent monetary expectations, network effects and deposit euroization are the legacy of past financial crises or the outflow of current policies and institutions in the region. Our findings suggest that deposit euroization in Eastern Europe can be partly tackled by prudent monetary and economic decisions by today's policymakers. The preferences of households for Euro deposits are partly driven by their distrust in the stability of their domestic currency, which in turn is related to their assessment of current policies and institutions. However, our findings also suggest that a stable monetary policy may not be sufficient to deal with the hysteresis of deposit euroization across the region. First, we confirm that the holding of foreign currency deposits has become a "habit" in the region. Second, we find that deposit euroization is still strongly influenced by households' experiences of financial crises in the 1990s.
Keywords: 330; Einlagengeschäft; Währungssubstitution; Euro; Osteuropa